Targeting Glucose Metabolism to Enhance Immunotherapy: Emerging Evidence on Intermittent Fasting and Calorie Restriction Mimetics - Turbitt, William J.; Demark-Wahnefried, Wendy; Peterson, Courtney M.; Norian, Lyse A. (Frontiers in Immunology, 2019)
There is growing interest in harnessing lifestyle and pharmaceutical interventions to boost immune function, reduce tumor growth, and improve cancer treatment efficacy while reducing treatment toxicity. Interventions targeting glucose metabolism are particularly promising, as they have the potential to directly inhibit tumor cell proliferation. However, because anti-tumor immune effector cells also rely on glycolysis to sustain their clonal expansion and function, it remains unclear whether glucose-modulating therapies will support or hinder anti-tumor immunity. In this perspective, we summarize a growing body of literature that evaluates the effects of intermittent fasting, calorie restriction mimetics, and anti-hyperglycemic agents on anti-tumor immunity and immunotherapy outcomes. Based on the limited data currently available, we contend that additional preclinical studies and clinical trials are warranted to address the effects of co-administration of anti-hyperglycemic agents or glucose-lowering lifestyle modifications on anti-tumor immunity and cancer treatment outcomes. We stress that there is currently insufficient evidence to provide recommendations regarding these interventions to cancer patients undergoing immunotherapy. However, if found to be safe and effective in clinical trials, interventions targeting glucose metabolism could act as low-cost combinatorial adjuvants for cancer patients receiving immune checkpoint blockade or other immunotherapies.